Evaluation of the location potential of commercial facilities as a place of refuge: A case study on facilities providing food in the Kii Peninsula - Ryo Sanuki; Eiji Satoh; Tatsuya Suzuki; Tohru Yoshikawa; Norio Maki (Japan Architectural Review, 2018)
Abstract The purpose of the study is to analyze the effect of establishing places of refuge in commercial facilities in addition to public facilities. To this end, the differences in accessibility of the places of refuge were analyzed across the Kii Peninsula and Matsuzaka City among various cases of facilities providing food. The analysis of the Kii Peninsula shows that supermarkets would be most useful. The analysis in Matsuzaka City shows that the facilities providing food would be useful to increase robustness and decrease the distance to refuges but less effective than refuge buildings on the coast in case of tsunami.